2021
DOI: 10.3389/fonc.2021.666059
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Macroscopic Fluorescence Lifetime Imaging of Brain Tumors

Abstract: Advanced stage glioma is the most aggressive form of malignant brain tumors with a short survival time. Real-time pathology assisted, or image guided surgical procedures that eliminate tumors promise to improve the clinical outcome and prolong the lives of patients. Our work is focused on the development of a rapid and sensitive assay for intraoperative diagnostics of glioma and identification of optical markers essential for differentiation between tumors and healthy brain tissues. We utilized fluorescence li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 52 publications
3
27
0
1
Order By: Relevance
“…Alfonso-Garcia et al intraoperatively demonstrated increased lifetimes for necrotic tissue respective to cortex as well as decreased lifetimes for an oligodendroglioma patient when comparing to the lifetimes of adjacent white matter (54). Higher mean NADH fluorescence lifetimes were also observed in glioblastomas respective to physiological brain (27,55). The interested reader is also referred to Marcu and Hartl (25).…”
Section: Discussionmentioning
confidence: 97%
“…Alfonso-Garcia et al intraoperatively demonstrated increased lifetimes for necrotic tissue respective to cortex as well as decreased lifetimes for an oligodendroglioma patient when comparing to the lifetimes of adjacent white matter (54). Higher mean NADH fluorescence lifetimes were also observed in glioblastomas respective to physiological brain (27,55). The interested reader is also referred to Marcu and Hartl (25).…”
Section: Discussionmentioning
confidence: 97%
“…For the broad clinical implementation of FLIM, application in large samples is particularly necessary. Here, wide-field FLIM and recent advances in establishing macroscopic FLIM imaging have been achieved, allowing the scanning of whole tissue samples [ 142 , 261 ].…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…Nanoparticles doped with appropriate lanthanide ions has proved to enhance NIR emission through energy trapping or suppress the up-conversion pathway ( Chen et al, 2017 ; Zhong et al, 2017 ). Fluorescence lifetime as a new dimension become highly useful in multichannel bioimaging ( Figure 2D ), which are independent of both colour and intensity ( Laviv et al, 2016 ; Fan et al, 2018 ; Zheng et al, 2018 ; Xie et al, 2020 ; Lukina et al, 2021 ; Luo et al, 2021 ). Zhang group designed NIR-II RENPs with tunable luminescence lifetimes for in vivo quantitative imaging ( Fan et al, 2018 ).…”
Section: Emission Mechanism Of Near-infrared Inorganic Nanomaterialsmentioning
confidence: 99%